Factors Associated With the Vaccination Behavior Among COVID-19 Vaccine Hesitant College Students in Wuhan, China: A Survey Based on Social Psychological Dimension - Xiong, Yifan; Zhao, Ying; Zhang, Tianyu; Wang, Qi; Liu, Jun-an (Frontiers in Public Health, 2022)
Background: During the COVID-19 pandemic, vaccine hesitancy (VH) on COVID-19 vaccination still exists in different populations, which has a negative impact on epidemic prevention and control. The objectives were to explore college students’ willingness to vaccinate, determine the factors influencing the vaccination behavior of students with COVID-19 vaccine hesitancy, and provide a basis for improving the compliance of college students with COVID-19 vaccination. Methods: The universities in Wuhan are categorized into three levels according to their comprehensive strength and randomly sampled at each level, of which ten universities were selected. A self-designed anonymous electronic questionnaire was distributed online from May 12 to 31, 2021 to investigate the hesitancy, vaccination status, and influencing factors of COVID-19 vaccination among college students in Wuhan. Results: Of the 1,617 participants (1,825 students received the electronic questionnaire) surveyed, 19.0% reported COVID-19 vaccine hesitancy. Among the vaccine-hesitant students, 40.1% were vaccinated against COVID-19. The binary logistic regression analysis shows that families’ attitudes “Uncertain” (odds ratio (OR)=0.258 [0.132–0.503]), vaccination risk psychology (OR=0.242 [0.079–0.747]) and wait-and-see mentality (OR=0.171 [0.068–0.468]) are negative factors for the vaccination behavior of hesitant students, while herd mentality (OR=7.512 [2.718–20.767]) and uncertainty of free policy’s impact on vaccine trust (OR=3.412 [1.547–7.527]) are positive factors. Conclusion: The vaccine hesitancy among college students in Wuhan was relatively high. Family support, herd mentality and free vaccination strategies can help improve vaccination among hesitant students, while vaccination risk psychology and “wait-and-see” psychology reduce the possibility of vaccination. The vaccination strategy of college students should be strengthened from the perspective of social psychological construction.